Pengaturan Pemilihan, Pemberhentian, Serta Konsekuensi Yuridis Terhadap Hasil Pemilihan Kepala Desa Di Kabupaten Flores Timur Tahun 2021 - Mourest Aryanto Kolobani; Kotan Y. Stefanus; Saryono Yohanes (CV. Multi Kreasi Media, 2023)
This research examines the Arrangements for the Election and Dismissal of Village Heads, as well as the Juridical Consequences for the Results of Village Head Elections in East Flores Regency in the Village Head election which will be held in 2021. The research objective is to find out and analyze: 1). Arrangement of Procedures for Election and Dismissal of Village Heads in East Flores Regency, 2). To find out and analyze the juridical consequences of the results of the Village Head Election in 2021 in East Flores district. The research method used is normative research using various secondary legal materials by combining materials from books and laws and regulations, legal theory, and expert opinions. The results of the study that 1). The implementation of village head elections in East Flores Regency during the Covid-19 pandemic used Regional Regulation of East Flores Regency Number 3 of 2020 from the preparation stage, nomination stage, voting stage and determination stage without accommodating Minister of Home Affairs Regulation Number 72 of 2020, 2). In the village head election stage in East Flores Regency in 2021, it is not in line with the Minister of Home Affairs Regulation Number 20 of 2020 which has resulted in the procedure for forming laws and accommodate regulations both philosophically, juridically and sociologically being formally flawed. Suggestions from the author, namely, in the preparation of Regional Regulations in the future it must the values ​​contained in the Minister of Home Affairs Regulations and the applicable laws and regulations so that in the preparation of Regional Regulations soyogia does not conflict with higher regulations.